Acceptance and use of the Information System of the National Immunization Program* - Valéria Conceição de Oliveira; Eliete Albano de Azevedo Guimarães; Gabriela Gonçalves Amaral; Talita Ingrid Magalhães Silva; Luciana Aparecida Fabriz; Ione Carvalho Pinto (Universidade de São Paulo, 2020)
Objective: to analyze the acceptance and use of the Information System of the National Immunization Program in primary health care vaccination rooms. Method: a unique case study of a qualitative approach in the light of the Unified Theory of Acceptance and Use of Technology. Data collection included an interview with 18 professionals responsible for the implementation of the information system, observation of vaccination rooms in 12 municipalities of the West Macro-region of Minas Gerais, selected from a preliminary study. Data was systematized and analyzed through Content Analysis. Results: the interviewees are satisfied with the usefulness and ease of the system usage, but do not have the same satisfaction with the organizational infrastructure due to the lack of computers and low Internet connectivity in the health units, as well as with the incipient training for the use of the information system and the lack of skills with the technology among the human resources. Conclusion: nursing professionals perceive advantages in the acceptance and use of the Information System of the National Immunization Program. It was clear that the vaccinated individual's history control and the decrease of records in paper are evidenced as facilitators of this acceptance. The system was considered reliable and secure.